Using structural equation modeling to explore the influences of physical activity, mental health, well-being, and loneliness on Douyin usage at bedtime - Luo, Hongcheng; Zhang, Xing; Su, Songpeng; Zhang, Mingyang; Yin, Mingyue; Feng, Siyuan; Peng, Rui; Li, Hansen (Frontiers in Public Health, 2024)
Douyin is the Chinese version of TikTok. Using Douyin at bedtime is a very common behavior among Douyin users. However, the reasons why users like using Douyin before sleep are yet unclear. We conducted a cross-section survey from January 1st to January 16th, 2023 to capture data to examine the associations of depression, anxiety, life satisfaction, well-being, loneliness, and physical activity with Douyin usage at bedtime. The mediation role of insomnia in these associations was examined. A total of 3,392 participants who met the inclusion criteria were included for analysis. Our structural equation modeling analysis showed that depression on (β = 0.08; p < 0.05), anxiety (β = 0.06; p < 0.05), and loneliness (β = 0.14; p < 0.05) were directly associated with increased Douyin usage at bedtime, and were also indirectly associated with Douyin usage through insomnia (depression: β = 0.18; p < 0.05, anxiety: β = 0.16; p < 0.05, and loneliness: β = 0.12; p < 0.05). Life satisfaction (β = −0.05; p < 0.05) and well-being (β = −0.20; p < 0.05) were directly associated with decreased Douyin usage at bedtime, and were also indirectly associated with Douyin usage through insomnia (life satisfaction: β = −0.09; p < 0.05, and well-being: β = −0.11; p < 0.05). However, physical activity was unexpectedly associated with increased Douyin usage at bedtime (β = 0.20; p < 0.05). In conclusion, our findings shed new light on the specific reasons why Douyin users like using Douyin at bedtime.